Nanovehicles in the improved treatment of infections due to brain-eating amoebae - Mungroo, Mohammad Ridwane; Khan, Naveed Ahmed; Ayaz, Anwar *; Siddiqui, Ruqaiyyah (Springer, 2022)
Pathogenic free-living amoebae are known to cause fatal central nervous system infections with extremely high mortality rates. High selectivity of the blood-brain barrier hampers delivery of drugs and untargeted delivery of drugs can cause severe side effects. Nanovehicles can be used for targeted drug delivery across the blood-brain barrier. Inorganic nanoparticles have been explored as carriers for various biomedical applications and can be modified with various ligands for efficient targeting and cell selectivity while lipid-based nanoparticles have been extensively used in the development of both precision and colloidal nanovehicles. Nanomicelles and polymeric nanoparticles can also serve as nanocarriers and may be modified so that responsiveness of the nanoparticles and release of the loads are linked to specific stimuli. These nanoparticles are discussed here in the context of the treatment of central nervous system infections due to pathogenic amoebae. It is anticipated that these novel strategies can be utilized in tandem with novel drug leads currently in the pipeline and yield in the development of much needed treatments against these devastating parasites.